Fatwa, Otoritas Agama, dan Tatanan Sosial: Membaca Kembali Realitas Hukum Islam tentang Homoseksualitas dan Tindak Pidana Seksual dalam Masyarakat Muslim Kontemporer - Qistina, Ulya; Al Kubra, Zainab; Herlina, Siti (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2026)
The rise of LGBT movements in Indonesia has caused public unrest and prompted the Indonesian Ulema Council (MUI) to issue Fatwa Number 57 of 2014 as a guideline in Islamic law. This article aims to analyze the legal foundations, scholarly views, and content of the MUI fatwa concerning LGBT issues. The method employed is library research using a normative-shar‘i approach, examining operational definitions, Qur’anic verses and hadiths, scholarly consensus (ijma‘), and the MUI fatwa in a descriptive-analytical manner. The results show that sihaq (lesbianism), liwath (sodomy/gay), and molestation are classified as abominable acts (fahishah) that are absolutely forbidden (haram) based on Surah al-A‘raf verses 80-81 and hadiths concerning the curse upon the people of Prophet Lut. Scholars unanimously agree (ijma‘) on this prohibition, although they differ regarding sanctions: the majority (including Imam Shafi‘i) prescribe the death penalty, while Imam Abu Hanifah maintains that the punishment is ta‘zir (discretionary punishment). MUI Fatwa Number 57 of 2014 affirms the prohibition of LGBT activities, the invalidity of same-sex marriage, and recommends severe penalties up to the death penalty for perpetrators of sodomy, alongside rehabilitation and prevention efforts. In conclusion, the MUI fatwa serves as a moral compass for Indonesian Muslims to safeguard public interest and national resilience against moral decadence.